Impact of Integration Management on Construction Project Management Performance (Oil Refining Company) - Taresh Ejel, Ahmed; ., . (International Journal of Engineering and Technology, 2018)
The purpose of this study was to investigate the effect of project risk management. The statistical population of this study was made up of all employees of Oil Refinery Company, which number was 4652 persons. According to Morgan table, 351 individuals were selected and selected by simple random sampling method and participated in the research. In this research, two risk management project questionnaires, including four dimensions and 30 questions, were used. Validity of the questionnaires was confirmed by experts and their reliability was confirmed by Cronbach's alpha 0.82. Structural Equation Modeling Technique (AMOS-22) was used to test the research hypotheses. The results of the research showed that the project risk management dimensions are content, in terms of outcomes, in terms of activity and in terms of conditions.Â Â